Circular Economy in The Concept of Waste Management : Implementation of Community-Based Environmental Management - Yunisvita, Yunisvita; Selvaratnam, Doris Padmini; Robiani, Bernadette; Rohima, Siti; Bashir, Abdul; Apriani, Deassy; Yarsah, Waldi Novi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to identify the form of plastic waste management, analyze the optimal circular economy-based waste management scenario and prepare recommendations for sustainable circular economy-based waste management policies in Sungsang IV Village. The method of this community service activity is empowerment and coaching using the coding and theming approach methods. The target audience for this activity is 25 housewives. More optimal circular economy-based waste management in the future can provide a strategic direction to realize a waste management system that is not only effective and efficient, but also sustainable for the community and the environment. The application of a circular economy in plastic waste management offers a solution that not only addresses environmental problems but also provides social and economic benefits for the community. Based on the results of the activity, it was revealed that most participants were motivated and gained new skills in managing waste so that it has utility value. With a combination of educational approaches, infrastructure development, and community empowerment, Sungsang IV Village can become a model for sustainable circular economy-based waste management.Â